Financing of Social Services Towards the Challenges of the Local and Regional Development (European Journal of Marketing and Economics, 2023)
The research focuses on the changes in financing of social services at regional and local level in a market economy in Poland. The important problems are also efficiency issues which can be implemented in public sector entities in the process of supporting social and economic development. In the study there were applied analytical methods relating to the gathered empirical data and research methods related to determining the real impact of the self-government units on the processes of socio-economic development. The key part of the text is analysis of the empirical source data regarding financial potential and directions of expenditures of self-government. Previous research results showed that the development of social services in a market economy in Poland was mainly the result of activities the entities and agencies of the public sector, whose role was to support and stimulate the development. As a challenge for the future it can be indicated strengthening the cooperation with entities of the third sector and sharing the responsibility both for the economic processes and social problems.
Keywords: social services, public finances, local and regional development.